Identification and Estimation in Binary Choice Models with Limited (Censored) Dependent Variables - Lee, Lung-Fei (Econometrica, 1979)
A class of statistical models which generate simultaneous equation models with both discrete and continuous endogenous variables is introduced. This class of models can also be regarded as a new class of switching simultaneous equation models which are of general interest. Identification and estimation problems are investigated. Several simple consistent two stage methods are proposed. The consistency of those estimators is proved. Two step maximum likelihood procedures are then developed. -Author